Penerapan Model PBL Berbantu Media Konkret untuk Meningkatkan Hasil Belajar Matematika Materi Satuan Panjang Kelas II SD Negeri Peterongan Semarang - Ratih Sukmadewi (Journal on Education, 2024)
The research in this paper aims to improve the learning outcomes of mathematics ateri unit length in class II SD Negeri Peterongan Semarang by applying the Problem Based Learning learning model assisted by concrete objects media. There were 19 students in grade II at SD Negeri Peterongan Semarang who became research subjects. This research was conducted using the Classroom Action research method which consists of Pre-Cycle, Cycle 1, and Cycle 2. This cycle consists of 4 stages, namely the planning stage, the action implementation stage, the observation stage, and the reflection stage. This study uses data collection techniques by conducting learning outcomes tests. From the results of the study revealed that second grade students of SD Negeri Peterongan Semarang achieved better learning outcomes when applying the PBL model assisted by concrete objects media. In cycle I, the acquisition of the percentage of learning completeness was 79% with an average score of 75.84 In cycle II, the percentage of learning experienced a significant increase of 89% with an average score of 80.84. This shows that there is an increase in the percentage of completeness by 10% and an increase in the average score by 5.0. So, it can be concluded that the PBL model assisted by concrete objects can improve the learning outcomes of mathematics unit length material in class II SD Negeri Peterongan Semarang.